Modelling and Solution of Trapezoidal Variable Orifice Flow Meter: 3D Fluid - Structure Interaction - Shamkhi, Rana K.; Ghalambaz, Mohammad; Ismael, Muneer A. (Basrah Journal for Engineering Sciences, 2025)
Gas flow measurements are pivotal in several medical applications. For instance, mechanical ventilators and respiratory monitoring applications need flowmeters with strict requirements. This study is concerned with a three-dimensional computational fluid dynamics (CFD) analysis. The CFD methodology was confirmed by analyzing the flow characteristics of flexible membrane with trapezoidal orifice plates. Variable area orifice meters (VAOMs) are increasingly being embraced in respiratory monitoring applications, employed in the context of mechanical ventilation within medical settings. Each system integrates a flexible orifice plate within the conduit. The simulations are conducted considering realistic deformations in structure through two-way fluid-structure interactions (FSI) using the Arbitrary-Lagrangian-Eulerian (ALE) approach. This research paper analyzes using the finite volume method (FVM). A thorough numerical simulation was performed for the turbulence models. The orifice’s thickness and shape significantly influence pressure drop and deflection.